Breast Cancer and Cervix Cancer Awareness, and Cancer Early Detection: A Community Service Program - Sahputri, Juwita; Azhari, Teuku; Millizia, Anna; Mellaratna, Wizar Putri; Rizka, Adi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Breast cancer awareness is a critical component of women's health promotion, aiming to increase knowledge about the disease, its risk factors, and early detection methods. This program was designed to raise awareness about breast cancer among women through information dissemination, leaflets, and pre-test and post-test evaluations. Drawing on existing research, the program emphasizes the importance of early detection through regular self-examination and screening. Studies have shown that public health campaigns can effectively initiate behavior change and improve health beliefs related to breast cancer screening. By leveraging insights from previous campaigns and research, this program seeks to empower women to prioritize their breast health, enhance awareness, and promote early detection strategies. The abstract highlights the significance of tailored interventions, community engagement, and targeted awareness initiatives in addressing the growing concern of breast cancer among women.